ACARORUM CATALOGUS VII. Trombidiformes, Prostigmata, Raphignathoidea (Fam. Barbutiidae, Caligonellidae, Camerobiidae, Cryptognathidae, Dasythyreidae, Dytiscacaridae, Eupalopsellidae, Homocaligidae, Mecognathidae, Raphignathidae, Stigmaeidae, Xenocaligonellididae) - Petar Beron (Advanced Books)
The 7th volume of my series "Acarorum Catalogus" concerns the mite superfamily Raphignathoidea. The 12 families of this superfamily consist of 69 genera and some 1087 species and are being studied intensely, particularly by acarologists from China, South Africa, Turkey, Iran, Crimea and other countries or areas. Some members of the Raphignathoidea are suitable for biological pest control (Gerson & Smiley 1990, Gerson, Smiley & Ochoa, 2003).